Influence of organism’s individual resistance to hypoxia on the humoral immunity at the modeled experimental diffuse cardiosclerosis - Saturska, Hanna Stepanivna; Bondarenko, Yurii Ivanovych; Potikha, Natalia Yaroslavivna (Journal of Education, Health and Sport, 2015)
Saturska H. S., Bondarenko Yu. I., Potikha N. Ya. Влияние индивидуальной резистентности организма к гипоксии на состояние гуморального иммунитета при смоделированном экспериментальном диффузном кардиосклерозе = Influence of organism’s individual resistance to hypoxia on the humoral immunity at the modeled experimental diffuse cardiosclerosis. Journal of Education, Health and Sport. 2015;5(3):207-217. ISSN 2391-8306. DOI: 10.5281/zenodo.16370 http://ojs.ukw.edu.pl/index.php/johs/article/view/2015%3B5%283%29%3A207-217 https://pbn.nauka.gov.pl/works/550036 http://dx.doi.org/10.5281/zenodo.16370 Formerly Journal of Health Sciences. ISSN 1429-9623 / 2300-665X. Archives 2011 – 2014 http://journal.rsw.edu.pl/index.php/JHS/issue/archive Deklaracja. Specyfika i zawartość merytoryczna czasopisma nie ulega zmianie. Zgodnie z informacją MNiSW z dnia 2 czerwca 2014 r., że w roku 2014 nie będzie przeprowadzana ocena czasopism naukowych; czasopismo o zmienionym tytule otrzymuje tyle samo punktów co na wykazie czasopism naukowych z dnia 31 grudnia 2014 r. The journal has had 5 points in Ministry of Science and Higher Education of Poland parametric evaluation. Part B item 1089. (31.12.2014). © The Author (s) 2015; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland and Radom University in Radom, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/3.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/3.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 20.01.2014. Revised 27.02 УДК 616.12-004-02:616.152.21-06:612.017.1]-092.9 UDC 616.12-004-02:616.152.21-06:612.017.1]-092.9 ВЛИЯНИЕ ИНДИВИДУАЛЬНОЙ РЕЗИСТЕНТНОСТИ ОРГАНИЗМА К ГИПОКСИИ НА СОСТОЯНИЕ ГУМОРАЛЬНОГО ИММУНИТЕТА ПРИ СМОДЕЛИРОВАННОМ ЭКСПЕРИМЕНТАЛЬНОМ ДИФФУЗНОМ КАРДИОСКЛЕРОЗЕ Influence of organism’s individual resistance to hypoxia on the humoral immunity at the modeled experimental diffuse cardiosclerosis Сатурская А. С., Бондаренко Ю. И., Потиха Н. Я. Saturska H. S., Bondarenko Yu. I., Potikha N. Ya. ГВУЗ «Тернопольский государственный медицинский университет имени И.Я. Горбачевского МЗ Украины», г. Тернополь SHEI “I. Horbachevsky Ternopil State Medical University of the Ministry of Public Health of Ukraine”, Ternopil, Ukraine saturska.gs@gmail.com Ключевые слова: гипоксия, диффузный кардиосклероз, иммуноглобулины А, М, G. Key words: hypoxia, diffuse cardiosclerosis, immunoglobulins A, M, G. ВЛИЯНИЕ ИНДИВИДУАЛЬНОЙ РЕЗИСТЕНТНОСТИ ОРГАНИЗМА К ГИПОКСИИ НА СОСТОЯНИЕ ГУМОРАЛЬНОГО ИММУНИТЕТА ПРИ СМОДЕЛИРОВАННОМ ЭКСПЕРИМЕНТАЛЬНОМ ДИФФУЗНОМ КАРДИОСКЛЕРОЗЕ Сатурская А.С., Бондаренко Ю.И., Потиха Н.Я. ГВУЗ «Тернопольский государственный медицинский университет имени И.Я. Горбачевского МЗ Украины», г. Тернополь saturska.gs@gmail.com В статье исследовано и проанализировано выявленные изменения содержания Ig M, Ig G, Ig A при сформированном диффузном ишемически-некротическом кардиосклерозе (этап наблюдения 30 суток), которые существенно зависят от резистентности животных к гипоксии. Выявлено, что моделирование диффузного кардиосклероза сопровождается увеличением содержания Ig G в сыворотке крови у животных с низкой и средней устойчивостью к гипоксии, а у высокоустойчивых к гипоксии животных достоверно не отличается от показателя группы контроля. Содержание Ig M и Ig A при моделировании диффузного кардиосклероза у животных всех экспериментальных групп уменьшено, что свидельствует об угнетении гуморального звена иммунитета на данном этапе, что наиболее выражено у животных с низкой устойчивостью к гипоксии. INFLUENCE OF ORGANISM’S INDIVIDUAL RESISTANCE TO HYPOXIA ON THE HUMORAL IMMUNITY AT THE MODELED EXPERIMENTAL DIFFUSE CARDIOSCLEROSIS Saturska H.S., Bondarenko Yu.I., Potikha N.Ya. SHEI “I. Horbachevsky Ternopil State Medical University of the Ministry of Public Health of Ukraine”, Ternopil, Ukraine saturska.gs@gmail.com The article studies and analyzes the changes identified in the Ig M, Ig G, Ig A content formed with diffuse ischemic-necrotic cardiosclerosis at the observation stage of 30 days, which depend significantly on the resistance of animals to hypoxia. It is shown that the modeling of diffuse cardiosclerosis is accompanied by increase of Ig G content in blood serum of animals with low and medium resistance to hypoxia. The Ig G content in animals with high resistance to hypoxia was not significantly different from its level in the control group. Content of Ig M and Ig A at modeling of diffuse cardiosclerosis in all experimental groups of animals is reduced, which testifies to the inhibition of humoral immunity at this stage, which is most pronounced in animals with low resistance to hypoxia.